1980
DOI: 10.1111/j.1600-0722.1980.tb01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2‐deoxy D‐glucose and other sugar analogues on acid production from sugars by human dental plaque bacteria

Abstract: – Solutions (10–25 μM) of D‐glucose, N‐acetyl‐D‐glucosamine, D‐fructose, sucrose, maltose, lactose and maltotriose were readily metabolised to acid (140–250 μmol H+ wet g−1h−1) by anacrobic suspensions of fresh plaque at pH 7.5. D‐Mannose, D‐galactose, D‐glucosamine and trehalose were broken down more slowly (35–115 μmol H+ wet g−1h−1). Inhibition of this acid production occurred on adding excess amounts of 2‐deoxy‐D‐glucose or 5‐thio‐D‐glucose. Similarly, excess amounts of cellobiose specifically inhibited ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
1
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
3
10
1
1
Order By: Relevance
“…Plaque bacteria like mutans streptococci and lactobacilli use the phosphoenolpyruvate-phosphotransferase system for the uptake of mono-and disaccharides [Ajdic and Pham, 2007;Barrangou et al, 2006]. Therefore, it is not surprising that the K 0.5 values obtained for L. paracasei tolerans (11 mol l -1 ) and L. rhamnosus (14 mol l -1 ) are in accordance with comparable data for S. mutans (20 mol l -1 [Stoesser, 1984]) and dental plaque (12 mol l -1 [Stoesser, 1984], 20 mol l -1 [Roberts and Hayes, 1980]). In contrast, sugar uptake of C. albicans is dependent on the H + -ATPase system which is apparently activated at a 50-fold higher concentration of glucose.…”
Section: Discussionsupporting
confidence: 76%
“…Plaque bacteria like mutans streptococci and lactobacilli use the phosphoenolpyruvate-phosphotransferase system for the uptake of mono-and disaccharides [Ajdic and Pham, 2007;Barrangou et al, 2006]. Therefore, it is not surprising that the K 0.5 values obtained for L. paracasei tolerans (11 mol l -1 ) and L. rhamnosus (14 mol l -1 ) are in accordance with comparable data for S. mutans (20 mol l -1 [Stoesser, 1984]) and dental plaque (12 mol l -1 [Stoesser, 1984], 20 mol l -1 [Roberts and Hayes, 1980]). In contrast, sugar uptake of C. albicans is dependent on the H + -ATPase system which is apparently activated at a 50-fold higher concentration of glucose.…”
Section: Discussionsupporting
confidence: 76%
“…Figure 1 shows that the rate of glucose incorporation was greater than the incorporation of other sugars. This is in agreement with the findings of Roberts and Hayes [1980] that glucose was the sug ar which gave the greatest rate of acid pro duction when added to plaque suspensions. In addition, the glucose concentration which gave half the maximum rate of acid produc tion (20 fiM) is of the same order as that which gave half the maximum rate of glu cose incorporation in the present work (41 iiM; fig.…”
Section: Incorporation Of Glucose Fructose Sucrose and 2-deoxyglucosesupporting
confidence: 82%
“…Since isomaltulose is only slightly decomposed by m icroorganisms (e.g. Streptococcus mutans, mitis, sanguis, salivarius) [von Gehring, 1973;Ohta and Takazoe, 1983] and plaque suspensions [Roberts and Hayes, 1980;Takazoe et al, 1982a], an occasional consum ption of isom altulose may not lower the plaque pH appreciably. According to Roberts and Hayes [1980], oligosaccharides containing the a -1-6 linkage (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that isomaltulose is slowly fermented by Streptococcus mutans and dental plaque suspensions [von Gehring, 1973;Roberts and Hayes, 1980;Ohta and Takazoe, 1983;Maki et al, 1983].…”
mentioning
confidence: 99%